Assessment of the process performance of produced water treatment with ceramic membranes through integration of online oil-monitor - Kerker, S. J.; Ebrahimi, M.; Hild, J.; Schmidt, A. A.; Czermak, Peter (My University, 2013)
In oilfield produced water treatment with ceramic membranes, process efficiency is characterized by the specific permeate flux and by the oil separation performance. Apart from the membrane properties, the permeate flux during filtration of oily wastewaters is known to be strongly dependent on the constituents of the feed solution, as well as on process conditions, e.g. trans-membrane pressure (TMP) and cross-flow velocity (CFV). In the current investigation tubular ceramic ultrafiltration membranes with a nominal molecular weight cut-off of 20 kD were evaluated for oilfield produced water treatment. The oil separation performance of the ceramic membrane was monitored online with an innovative oil-in-water monitor developed by DECKMA HAMBURG GmbH. The oil contamination in the feed and permeate stream could be measured continuously and recorded in the range from 0 to 200 ppm with a resolution of 1 ppm. With the ceramic membranes an oil removal up to 99 % could be achieved with permeate qualities of less than 1 ppm residual oil, meeting the regulations for discharge in most areas. Under certain process conditions, (high CFV, low TMP) permeate fluxes of 195 l*m-2*h-1 with virtually no flux decline over 12 h could be reached, promising long time operation with reduced number of cleaning cycles.
Keywords: Ceramic membrane; Produced water treatment; Oil content; Online monitoring